Assessment of Infrastructure Resilience in the 2015 Gorkha, Nepal, Earthquake. (December 2017) - Zhu, Jin; Manandhar, Barsha; Truong, Jenny; Ganapati, N. Emel; Pradhananga, Nipesh; Davidson, Rachel A.; Mostafavi, Ali
Despite many studies on infrastructure resilience in the existing literature, there is a limited empirical understanding of disaster resilience in the context of intermittent infrastructure systems. To fill this knowledge gap, our study provides an example assessment of the resilience of Kathmandu Valley's electricity and water supply infrastructure systems in the 2015 Gorkha earthquake. The study is based on qualitative data collected over a period of one year following the earthquake, obtained through in-depth interviews (n = 52), a focus group, and a review of secondary sources. A resilience assessment framework that includes eight factors adapted from existing studies—vulnerability, anticipation, redundancy, adaptive capacity, rapidity, resourcefulness, cross-scale interactions, and learning culture—was used for the data analysis. The characteristics of intermittent infrastructure systems pertaining to resilience identified in this study could have important implications for engineers and decision makers in developing communities to better design and maintain infrastructure in the face of disasters.